Enhanced Experience in Research, Entrepreneurship, and University Social Responsibility for Technology-Based Entrepreneurship - Esquicha-Tejada, José; Sanchez-Orihuela, Alana; Cuya-Zevallos, Carla; Rosas-Paredes, Karina; Sapaico-del-Castillo, Cesar; Villanueva-Paredes, Grace (LACCEI, 2024)
Having training programs for strengthening research, entrepreneurship, and university social responsibility based on technology-based entrepreneurship is vital for a country's economic contribution. This research proposes a program that enables the formation of multidisciplinary teams of university students, allowing them to participate in three different categories: research, entrepreneurship, and university social responsibility. With the proposed methodology, participants reported a satisfaction rate of 88.5% with the program, highlighting the positive impact of raising awareness among participants to achieve the strengthening of the university innovation and entrepreneurship ecosystem.